Tasawuf Terapan dalam Rutinitas Yasinan dan Diba’an: Terapi Ketenangan Hati bagi Mahasiswa Pesantren Fatkhul Mu’in Purwokerto - Eka Dewi, Maesaroh (Theofani: Journal of Islamic Studies and Scholarly Discourse, 2025)
This article explores how applied Sufism practices through the routines of Yasinan and Diba’an shape inner peace among students residing at Pondok Pesantren Fatkhul Mu’in Purwokerto. Amidst the academic, social, and spiritual pressures faced by these students, such religious activities serve as contemplative spaces that positively impact their emotional stability. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observation, and documentation. The findings indicate that students who consistently participate in Yasinan and Diba’an experience reduced anxiety levels, improved concentration in learning, and a greater sense of calm in dealing with life’s challenges. The spiritual processes within these rituals foster a state of transcendental awareness that nurtures inner tranquility. These findings affirm that pesantren religious traditions are not merely cultural expressions, but also hold potential as relevant psychospiritual therapy in supporting students’ mental health.